2017
DOI: 10.1073/pnas.1701652114
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of local changes along the timescale processing hierarchy

Abstract: Small changes in word choice can lead to dramatically different interpretations of narratives. How does the brain accumulate and integrate such local changes to construct unique neural representations for different stories? In this study, we created two distinct narratives by changing only a few words in each sentence (e.g., "he" to "she" or "sobbing" to "laughing") while preserving the grammatical structure across stories. We then measured changes in neural responses between the two stories. We found that dif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
92
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 46 publications
5
92
0
Order By: Relevance
“…Furthermore, comprehension studies have provided evidence in support of a cortical processing Schematic representation illustrating the fact that identical probabilities of syntagmatic co-occurrence (e.g., p(VERB1 + OBJECT1) = 0.20 and p (VERB2 + OBJECT1) = 0.20) need not amount to equal expectedness, since paradigmatic competition between different options (here: objects) will also play a role. Thus, OBJECT1 is the paradigmatically dispreferred competitor after VERB1, while it is the preferred option after VERB2 hierarchy that is consistent with the functional scales of the MSIT framework (Grafton, 2009;de Heer, Huth, Griffiths, Gallant, & Theunissen, 2017;Yeshurun, Nguyen, & Hasson, 2017).…”
Section: Multiscale Predictive Processing Across Domainsmentioning
confidence: 60%
See 1 more Smart Citation
“…Furthermore, comprehension studies have provided evidence in support of a cortical processing Schematic representation illustrating the fact that identical probabilities of syntagmatic co-occurrence (e.g., p(VERB1 + OBJECT1) = 0.20 and p (VERB2 + OBJECT1) = 0.20) need not amount to equal expectedness, since paradigmatic competition between different options (here: objects) will also play a role. Thus, OBJECT1 is the paradigmatically dispreferred competitor after VERB1, while it is the preferred option after VERB2 hierarchy that is consistent with the functional scales of the MSIT framework (Grafton, 2009;de Heer, Huth, Griffiths, Gallant, & Theunissen, 2017;Yeshurun, Nguyen, & Hasson, 2017).…”
Section: Multiscale Predictive Processing Across Domainsmentioning
confidence: 60%
“…Consistent with this claim, recent language and action processing studies have revealed extensive neural activation overlap between the production and comprehension processes within each domain, respectively (Grafton, ; Silbert, Honey, Simony, Poeppel, & Hasson, ). Furthermore, comprehension studies have provided evidence in support of a cortical processing hierarchy that is consistent with the functional scales of the MSIT framework (Grafton, ; de Heer, Huth, Griffiths, Gallant, & Theunissen, ; Yeshurun, Nguyen, & Hasson, ).…”
Section: Multiscale Predictive Processing Across Domainsmentioning
confidence: 61%
“…We developed a set of models to explain prior measurements of neural responses to intact and temporally scrambled stimuli (e.g. Lerner et al, 2011, also Baldassano et al, 2017Chen et al, 2017;Farbood et al, 2015;Hasson et al, 2008;Honey et al, 2012;Simony et al, 2016;Yeshurun et al, 2017). In particular, lower-level sensory regions should display contextinvariant responses to the intact and scrambled narratives: the response to a particular input segment (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Further posterior and anterior temporal regions could only track lists of sentences or paragraphs (but not words), indicative of sensitivity to phraseor sentence-level information. And, finally, some inferior frontal regions exhibited this same pattern of sensitivity to phrase/sentence information, with yet others reliably tracking only paragraph (but not sentence) lists, indicative of sensitivity to information above the sentence level (a long TRW).This hierarchy of integration timescales is an appealing organizing principle of the core language network (DeWitt and Rauschecker, 2012;Bornkessel-Schlesewsky et al, 2015;Hasson et al, 2015;Chen et al, 2016;Baldassano et al, 2017;Yeshurun et al, 2017a;Sheng et al, 2018). Nevertheless, there are several reasons to question the putative correspondence between this hierarchy and the set of language-selective cortical regions.…”
mentioning
confidence: 82%
“…This hierarchy of integration timescales is an appealing organizing principle of the core language network (DeWitt and Rauschecker, 2012;Bornkessel-Schlesewsky et al, 2015;Hasson et al, 2015;Chen et al, 2016;Baldassano et al, 2017;Yeshurun et al, 2017a;Sheng et al, 2018). Nevertheless, there are several reasons to question the putative correspondence between this hierarchy and the set of language-selective cortical regions.…”
Section: Highlightsmentioning
confidence: 99%